Effectiveness of Spiritual Emotional Freedom Technique (SEFT) in Improving Psychological Well-Being of Health Workers - Windyaningrum , Sertiana Dwi; Nashori, Fuad (Universitas Islam Indonesia, 2024)
Health workers are under high pressure to carry out their work. This results in physical and mental fatigue. One is the non-achievement of psychological well-being and decreased performance in health services. To overcome the decline in psychological well-being, complementary therapy in the form of Spiritual Emotional Freedom Technique (SEFT) is needed. SEFT is a therapy that combines psychological energy and spiritual power by using a tool in the form of tapping on the body. This study aimed to determine the effectiveness of SEFT therapy in improving the psychological well-being of health workers. This study used an experimental design, a Non-randomized Control Group Pretest-Posttest Design involving 30 health workers. The results showed that the experimental group who received SEFT intervention experienced increased psychological well-being compared to the control group who did not receive intervention treatment. Based on the results of the Wilcoxon test for pre-test and post-test in the experimental group, it can be concluded that SEFT is effective for improving the psychological well-being of health workers. Other variables such as personality, age, and environment are recommended to be controlled in future studies.